The Nature of Meaning of Stories in Conversation - Livia Polanyi (Studies in 20th & 21st Century Literature, 1981)
Although everyday stories told in the course of ongoing conversations are as open to multiple readings as many literary texts, the participants in the conversational storytelling situation must assign a meaning to a given telling of a story in order to facilitate the absorption of the story into the state of general talk which normally obtains. In the present paper, work done by the American linguistic school of narrative analysis (as begun by Labov and Waletzky and further developed by the author of this paper) is brought together with insights into conversational storytelling from ethno-methodological conversation analysts (Sacks, Jefferson, etc.) The meaning of a given telling of a story is shown to derive from both the structure of the story as told and the process of interpretation which goes on in the conversation after the telling. Special attention is paid to the «next story» which can follow the telling of a «first story» in a conversation. It is argued that the next story is crucially constrained by the first story, while the first story is assigned its meaning partially from the topic of the following one.
Keywords: Labov; Waletzky; linguistics; conversational storytelling; storytelling; ethno-methodological; Sacks; Jefferson